Exploring the Spatial Control of Topotactic Phase Transitions Using Vertically Oriented Epitaxial Interfaces - Zhang, Wenrui; Zhang, Jie; Cheng, Shaobo; Rouleau, Christopher M.; Kisslinger, Kim; Zhang, Lihua; Zhu, Yimei; Ward, Thomas Z.; Eres, Gyula (Nano-Micro Letters, 2021)
Engineering oxygen vacancy formation and distribution is a powerful route for controlling the oxygen sublattice evolution that affects diverse functional behavior. The controlling of the oxygen vacancy formation process is particularly important for inducing topotactic phase transitions that occur by transformation of the oxygen sublattice. Here we demonstrate an epitaxial nanocomposite approach for exploring the spatial control of topotactic phase transition from a pristine perovskite phase to an oxygen vacancy-ordered brownmillerite (BM) phase in a model oxide La0.7Sr0.3MnO3 (LSMO). Incorporating a minority phase NiO in LSMO films creates ultrahigh density of vertically aligned epitaxial interfaces that strongly influence the oxygen vacancy formation and distribution in LSMO. Combined structural characterizations reveal strong interactions between NiO and LSMO across the epitaxial interfaces leading to a topotactic phase transition in LSMO accompanied by significant morphology evolution in NiO. Using the NiO nominal ratio as a single control parameter, we obtain intermediate topotactic nanostructures with distinct distribution of the transformed LSMO-BM phase, which enables systematic tuning of magnetic and electrical transport properties. The use of self-assembled heterostructure interfaces by the epitaxial nanocomposite platform enables more versatile design of topotactic phase structures and correlated functionalities that are sensitive to oxygen vacancies. Highlights: 1 An epitaxial nanocomposite approach is developed for exploring spatial control of oxygen vacancy-driven topotactic phase transition of La0.7Sr0.3MnO3-x (LSMO). 2 The ultrahigh density of epitaxial interfaces created in the self-assembled LSMO-NiO nanocomposite films strongly influence the oxygen vacancy formation and topotactic phase distribution in LSMO. 3 The distinct intermediate topotactic nanostructures controlled by the NiO fraction broadens the tuning range of correlated magnetic and transport properties of LSMO.